Can Extraterritorial Jurisdiction Help Overcome Regulatory Gaps of Animal Law? Insights from Trophy Hunting - Charlotte Blattner (AJIL Unbound, 2017)
Cross-border trade, industry outsourcing, and increased animal migration are becoming pressing issues for numerous states and fundamentally challenge our conceptions of animal law as territorial. Instead of proposing that nations try to solve these problems by coming to agreement on low and mostly ineffective standards, this essay opens an unexplored and promising avenue for animal law: extraterritorial protection. Using the example of trophy hunting, the essay reveals the many established jurisdictional options that can help animal law to overcome regulatory gaps, and showcases how animal issues can thereby gain visibility on the international plane.